Higher Education and Regional Development Tales from Northern and Central Europe (Palgrave Studies in Global Higher Education,, 2018)
This book analyses the role of universities as critical actors in the socio-economic development of peripheral regions in Norway and the Czech Republic. Examining the ambiguities of the traditional mission of a university in comparison to contemporary demands, the editors and contributors move past single-case analyses to adopt an integrated conceptual and analytical framework. The authors question whether universities can indeed 'fix' the conditions of any region they operate in, as is a common assumption, by examining peripheral regions, many of which have been devastated by natural or man-made disasters. Simultaneously acknowledging the complexities at the heart of both higher education institutions and regions, this book brings together a set of critical contributions that shed light on how universities can fulfil their role in peripheral regions rather than knowledge-intensive cities and towns. This uniquely researched book will be of interest to students and scholars of higher education, universities and communities, and education policy.